Assessment of the Relationship Between Intention to Migrate With Workload and a Healthy Work Environment of Nurses - Tahmine Salehi; Mohammadsaeed Mirzaee; Shima Haghani; Nadia Salehinia (Iran University of Medical Sciences, 2023)
Background: Like other countries in the world, Iran is facing the problem of a shortage of nurses. Meanwhile, many Iranian nurses migrate to other countries every year. The present study aims to assess the relationships between migration intention, workload, and a healthy work environment for nurses. Methods: This cross-sectional correlational study was conducted in 2020 using a proportional stratified sampling of 360 nurses working in the Iran University of Medical Sciences (IUMS) teaching hospitals. The study data were collected through a demographic questionnaire, the nurses' intention to migrate questionnaire, the NASA task load index, and the American Association of Critical-Care Nurses Healthy Work Environment Assessment. In this study, we used the independent t-test, analysis of variance, and the Pearson correlation coefficient for data analysis at a significance level of <0.05 in SPSS software, version 16. Results: The Mean±SD intention to migrate score was 65.59±33.51. A weak but significant positive correlation existed between the intention to migrate and workload (r=0.166, P=0.002). There was an inverse and weak relationship between the intention to migrate and a healthy work environment (r=-0.160, P=0.002). There was also a significant relationship between the intention of nurses to migrate and their work experience (P=0.048) and employment status (P=0.001). Conclusion: The prevention of nurses' migration must be investigated thoroughly to determine the reasons. But according to the results of this study, providing a healthy work environment and maintaining the current workforce by providing the indicators desired by nurses may partly prevent excessive migration of nurses.